Effect of repetitive peripheral magnetic stimulation for patients with chronic stroke: a case report using an AB design - Itoh, Shota; Fujimura, Kenta; Imamura, Shogo; Itoh, Ryoka; Misawa, Yuma; Matsuda, Mii; Chikamori, Chisato; Tanikawa, Hiroki; Maeda, Hirofumi; Kagaya, Hitoshi (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveTo determine the effects of repetitive peripheral magnetic stimulation in a patient with chronic stroke.DesignCase report.PatientsA man in his 70s presented with left hemiplegia secondary to cerebral hemorrhage.MethodsAn AB design was used: phase A (sham stimulation) and phase B (active stimulation). Magnetic stimulation was applied using a peripheral magnetic stimulator (Pathleader™, IFG, Sendai, Japan). Outcomes were assessed at four points: before the intervention, after phase A, after phase B, and at follow-up (3 weeks after phase B) using the Modified Ashworth Scale, range of motion, Fugl-Meyer Assessment, Simple Test for Evaluating Hand Function, and Canadian Occupational Performance Measures.ResultsThe Modified Ashworth Scale score for the wrist extensor remained unchanged in phase A but improved after phase B and was sustained at follow-up. The range of motion showed no change. The Fugl-Meyer Assessment scores were 40, 41, 44, and 45, respectively, and the Simple Test for Evaluating Hand Function scores were 1, 4, 3, and 5, respectively, at the four time points. One Canadian Occupational Performance Measure item improved after phase B and remained stable.ConclusionIn patients with chronic stroke and severe hemiplegia, repetitive peripheral magnetic stimulation may be effective in reducing spasticity and improving motor function.